Combating corruption in the Philippines are we plundering our chances or doing it bettter?. - Gutierrez, Merceditas N.; Marcelo, Simeon V.; Mercado, Edwin E.; Abueva, Jose V.; Badilla, Raul Dominic I.; Coronel, Sheila S.; Garcia, Ermin F. Jr. (Quezon City National College of Public Administration and Governance, 2005)
This CD-ROM contains related literature and studies on corruption, primer on combating corruption and brief descriptions of the speakers, reactors and organizers of the 6th Diliman Governance Forum held at the UPNCPAG Assembly Hall last March 16, 2005. Speakers and reactors include Ombudsman Simeon V. Marcelo, Rev. Fr. Edwin E. Mercado, Sec. Merceditas N. Gutierrez, Ms. Sheila S. Coronel, Mr. Raul Dominic I. Badilla, Mr. Ermin F. Garcia, Jr., and Dr. Jose V. Abueva.
6th DGF kit -- Related literature and studies on corruption.
Conducted by National College of Public Administration and Governance, University of the Philippines, Philippine Society for Public Administration.
In cooperation with The British Council- UP Higher Education Link, University of Manchester, United Nations Development Programme, Class PA 241 (Public Policy and Program Administration), Class PA 244 (Policy Process).
PDF format.
System requirements: Acrobat Reader.
Keywords: Political corruption--Philippines--Congresses.